2020
DOI: 10.1038/s41533-020-00205-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing LAMA with LABA and LTRA as add-on therapies in primary care asthma management

Abstract: The Global Initiative for Asthma recommends a stepwise approach to adjust asthma treatment to the needs of individual patients; inhaled corticosteroids (ICS) remain the core pharmacological treatment. However, many patients remain poorly controlled, and evidence-based algorithms to decide on the best order and rationale for add-on therapies are lacking. We explore the challenges of asthma management in primary care and review outcomes from randomised controlled trials and meta-analyses comparing the long-actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 87 publications
0
6
0
1
Order By: Relevance
“…Furthermore, more than half of the patients with asthma were prescribed LTRA for a long duration; this is in line with LTRA use in other countries – for example, a retrospective cohort study of medical and pharmacy claims database in the United States showed that 62% of patients who initiated triple therapy, received LTRA. 23 Evidence from several studies that investigated the efficacy of ICS/LABA compared with ICS + LTRA showed superior benefits on lung function and exacerbations in favour of ICS/LABA; 24,25 however, we could not compare the effects of ICS + LTRA and ICS/LABA in this study due to overlapping prescriptions. Despite enrolling patients managed at tertiary-care centres, our study included multiple centres with wide geographical representation across China, and the frequency of SABA over-prescription was substantially lower than that observed among patients managed at tertiary-care centres in other countries.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, more than half of the patients with asthma were prescribed LTRA for a long duration; this is in line with LTRA use in other countries – for example, a retrospective cohort study of medical and pharmacy claims database in the United States showed that 62% of patients who initiated triple therapy, received LTRA. 23 Evidence from several studies that investigated the efficacy of ICS/LABA compared with ICS + LTRA showed superior benefits on lung function and exacerbations in favour of ICS/LABA; 24,25 however, we could not compare the effects of ICS + LTRA and ICS/LABA in this study due to overlapping prescriptions. Despite enrolling patients managed at tertiary-care centres, our study included multiple centres with wide geographical representation across China, and the frequency of SABA over-prescription was substantially lower than that observed among patients managed at tertiary-care centres in other countries.…”
Section: Discussionmentioning
confidence: 93%
“…There are now at least three studies of a direct comparison of LAMA to LABA, all tiotropium versus salmeterol, when added to ICS in severe 22 , moderate 27 , and mild-moderate 26 asthma, all showing a similar or greater FEV 1 response with the LAMA. A recent review by Kaplan et al (2020) concluded that LAMAs yield a greater improvement in lung function than LABAs, and are as effective as LABAs with respect to achieving asthma control and preventing exacerbations 42 . Some patients have side effects on LABAs, and some patients respond better to either one of both drugs, making the use of LAMAs a viable alternative to LABA 43 .…”
Section: Positioningmentioning
confidence: 99%
“…Bronchodilators such as β2 agonists and muscarinic antagonists as add-on ICS can improve lung function, control symptoms, and reduce exacerbations. 5 β2 agonist can be combined with ICS if the condition of asthma exacerbation is moderate or severe. Meanwhile, patients with mild asthma can be used β2 agonist and low dose ICS combination when asthma exacerbations occur or before physical activity that can trigger worsening asthma symptoms.…”
Section: Introductionmentioning
confidence: 99%